Self-interest before Adam Smith: A genealogy of economic science - Force, Pierre (Cambridge University, 2013)
A study of the history of the concept of self-interest before Adam Smith, in order to understand what it meant when Adam Smith used it as an axiom in The Wealth of Nations. The author shows that Smith's theory refutes the 'selfish hypothesis' yet integrates it at the same time.